Azole-Based Compounds That Are Active against Candida Biofilm: In Vitro, In Vivo and In Silico Studies - Simone Carradori; Alessandra Ammazzalorso; Barbara De Filippis; Ahmet Fatih Şahin; Atilla Akdemir; Anastasia Orekhova; Graziana Bonincontro; Giovanna Simonetti (MDPI AG, 2022)
Fungal pathogens, including Candida spp., Aspergillus spp. and dermatophytes, cause more than a billion human infections every year. A large library of imidazole- and triazole-based compounds were in vitro screened for their antifungal activity against C. albicans, C. glabrata, C. krusei, A. fumigatus and dermatophytes, such as Microsporum gypseum, Trichophyton rubrum and Trichophyton mentagrophytes. The imidazole carbamate 12 emerged as the most active compound, showing a valuable antifungal activity against C. glabrata (MIC 1-16 μg/mL) and C. krusei (MIC 4-24 μg/mL). No activity against A. fumigatus or the dermatophytes was observed among all the tested compounds. The compound 12 inhibited the formation of C. albicans, C. glabrata and C. krusei biofilms and reduced the mature Candida biofilm. In the Galleria mellonella larvae, 12 showed a significant reduction in the Candida infection, together with a lack of toxicity at the concentration used to activate its antifungal activity. Moreover, the in silico prediction of the putative targets revealed that the concurrent presence of the imidazole core, the carbamate and the p-chlorophenyl is important for providing a strong affinity for lanosterol 14α-demethylase (CgCYP51a1) and the fungal carbonic anhydrase (CgNce103), the S-enantiomer being more productive in these interactions.